Estimated metabolic and mechanical demands during different small-sided games in elite soccer players - Gaudino, P.; Alberti, G.; Iaia, F. M. (Human Movement Science, 2014)
The present study examined the extent to which game format (possession play, SSG-P and game with regular goals and goalkeepers, SSG-G) and the number of players (5, 7 and 10 a-side) influence the physical demands of small-sided soccer games (SSGs) in elite soccer players. Training data were collected during the in-season period from 26 English Premier League outfield players using global positioning system technology. Total distance covered, distance at different speed categories and maximal speed were calculated. In addition, we focused on changes in velocity by reporting the number of accelerations and decelerations carried out during the SSGs (divided in two categories: moderate and high) and the absolute maximal values of acceleration and deceleration achieved. By taking into account these parameters besides speed and distance values, estimated energy expenditure and average metabolic power and distance covered at different metabolic power categories were calculated. All variables were normalized by time (i.e., 4 min). The main findings were that the total distance, distances run at high speed (>14.4 km h-1) as well as absolute maximum velocity, maximum acceleration and maximum deceleration increased with pitch size (10v10 > 7v7 > 5v5; p < .05). Furthermore, total distance, very high (19.8-25.2 km h-1) and maximal (>25.2 km h-1) speed distances, absolute maximal velocity and maximum acceleration and deceleration were higher in SSG-G than in SSG-P (p < .001). On the other hand, the number of moderate (2-3 m s-2) accelerations and decelerations as well as the total number of changes in velocity were greater as the pitch dimensions decreased (i.e., 5v5 > 7v7 > 10v10; p < .001) in both SSG-G and SSG-P. In addition, predicted energy cost, average metabolic power and distance covered at every metabolic power categories were higher in SSG-P compared to SSG-G and in big than in small pitch areas (p < .05). A detailed analysis of these drills is pivotal in contemporary football as it enables an in depth understanding of the workload imposed on each player which consequently has practical implications for the prescription of the adequate type and amount of stimulus during exercise training.